Adquisición De Datos De Magnitudes En Un Sistema Oleohidráulico Para Su Control Y Monitoreo En Un Laboratorio Remoto De Instrumentación Virtual De Código Abierto - Romero, Telmo Jesús Moreno; Chávez, Javier Enrique Orna; Avilés, Hugo Oswaldo Moreno; Barragán, Ãlvaro Gonzalo Aguinaga; Cobos, Nelson Gustavo Jara (European Scientific Journal, ESJ, 2017)
The present research analyzes the state of the art of remote laboratories and their use in teaching and industry. In addition, the aim of this study is to develop a test bench to control and maintain, in optimal conditions, the operating parameters of a hydraulic oil system through an open source virtual platform. This equipment will analyze the behavior of an external gear pump which will enable us to make comparisons of mathematical models to predict the flow rate and compare it with that obtained in real time through the test bench. The analysis starts with a theoretical revision that is used for defining the variables to be controlled in the test bench. It is also used to propose a methodology that allows reaching the objectives raised.